Precipitation variation since 1748 CE in the central Lesser Khingan Mountains, Northeast China - Mingqi Li; Guofu Deng; Xuemei Shao; Zhi-Yong Yin (Ecological Indicators, 2021)
Inter-annual variations of precipitation play important roles in forest management and agricultural production. This study presents a 270-year precipitation reconstruction of winter to early growing season for the central Lesser Khingan Mountains, Northeast China based on tree-ring width data of 99 tree-ring cores of Korean pine from two sampling sites near Yichun city. The reconstruction explained 46% of the variance in precipitation from the previous October to current June during the calibration period CE 1959–2017. At decadal scale, we identified four dry periods that occurred during CE 1748–1759, 1774–1786, 1881–1886 and 1918–1924, and four wet periods occurring during CE 1790–1795, 1818–1824, 1852–1859 and 2008–2017, and the period CE 2008–2017 was the wettest in the past 270 years. Power spectral analysis and wavelet analysis revealed cyclic patterns on the inter-annual (2–3 years) and inter-decadal (~11 and ~30–60 years) timescales in the reconstructed series. In addition, the Asian polar vortex has an important effect on the precipitation in our study area.